PENGARUH PENAMBAHAN MINERAL Fe DAN SISTEM BUDIDAYA TERHADAP KEMATANGAN GONAD IKAN SELAIS (Ompok Hypopthalmus) - Andy Sabara; Usman Muhammad Tang; Sukendi Sukendi (Berkala Perikanan Terubuk, 2016)
This study was aimed to Analyzed the Fe supplementation on gonadal maturity of selais, then to Analyzed the effect of culture system to accelerate gonadal maturation of selais, and the last aimed was to Analyzed the interaction between culture system with Fe amount. The method used is an experimental method. The design with two factors: the Fe Supplementation and culture system. Factor 1 is the feed formulation with 4 supplementation levels of Fe (synthetic), Fe From shell, Fe supplementation from anchovies and control without the Fe supplementation. Factor 2 is culture system which are stagnant ad flowing water. The results showed that Fe supplementation and culture systems affect the fish growth, but their interaction was not significant. The best treatment was obtained in the treatment of Fe supplementation from shellfish and water flowing systems.